Mitogen-activated protein kinases promote WNT/beta-catenin signaling via phosphorylation of LRP6 - Červenka, Igor; Wolf, Joshua; Mašek, Jan; Krejci, Pavel; Wilcox, William R; Kozubík, Alois; Schulte, Gunnar; Gutkind, J Silvio; Bryja, Vítězslav (Molecular and cellular biology, 2011)
LDL-related protein 6 (LRP6) is a coreceptor of WNTs and a key regulator of the WNT/β-catenin pathway. Upon activation, LRP6 is phosphorylated within its intracellular PPPS/TP motifs. These phosphorylated motifs are required to recruit axin and to inhibit glycogen synthase kinase 3 (GSK3), two basic components of the β-catenin destruction complex. On the basis of a kinome-wide small interfering RNA (siRNA) screen and confirmative biochemical analysis, we show that several proline-directed mitogen-activated protein kinases (MAPKs), such as p38, ERK1/2, and JNK1 are sufficient and required for the phosphorylation of PPPS/TP motifs of LRP6. External stimuli, which control the activity of MAPKs, such as phorbol esters and fibroblast growth factor 2 (FGF2) control the choice of the LRP6-PPPS/TP kinase and regulate the amplitude of LRP6 phosphorylation and WNT/β-catenin-dependent transcription. Our findings suggest that cells not only recruit one dedicated LRP6 kinase but rather select their LRP6 kinase depending on cell type and the external stimulus. Moreover, direct phosphorylation of LRP6 by MAPKs provides a unique point for convergence between WNT/β-catenin signaling and mitogenic pathways.
Keywords: Amino Acid Motifs; Low Density Lipoprotein Receptor-Related Protein-6; Cell Line; mitogenem aktivované proteinkinasy p38; fosforylace; Mitogen-Activated Protein Kinase 8; beta Catenin; aminokyselinové motivy; signální transdukce; Phosphorylation; proteiny Wnt; Receptors, LDL; Signal Transduction; MAP kinasový signální systém; mitogenem aktivovaná proteinkinasa 8; Wnt Proteins; RNA, Small Interfering; krysa rodu Rattus; MAP Kinase Signaling System; LDL receptor related protein 6; Animals; lidé; Mitogen-Activated Protein Kinases; p38 Mitogen-Activated Protein Kinases; Humans; malá interferující RNA; zvířata; Rats; proteiny související s LDL-receptory; nádorové buňky kultivované; buněčné linie; Tumor Cells, Cultured; LDL-receptory; mitogenem aktivované proteinkinasy; beta-katenin; LDL-Receptor Related Proteins